OPTIMALISASI OFFICIAL WEBSITE PT. XL AXIATA DALAM MENGKOMUNIKASIKAN PESAN CSR - Alya Rizqi, (2023)
Companies are required not only to carry out CSR as a social duty, but also to convey the results of CSR programs that the company has carried out. The official website is used by XL Axiata to send CSR messaging to the audience. The purpose of this research is to decipher how XL Axiata official website usage when conveying CSR messages to stakeholders. The Media Richness Theory was utilized to further explain this research. This study is a qualitative descriptive study that use the qualitative content analysis methodology. This study included primary data sources, such as documentation from XL Axiata's official website, and secondary data sources, such as literature searches and examinations of online media documentation, among other things. The study's findings revealed that PT. XL Axiata uses official website as the company's media to communicate CSR optimally, hence every visitor who visits PT. XL Axiata can understand the CSR information provided by the company and the information presented inside the media can minimize the uncertainty or ambiguity of the company's CSR information.